Cambodia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper analyzes the potential impact of oil on economic growth and policy for Cambodia. It shows that a hypothetical moderately sized oil sector would have a significant, but not overwhelming, impact on macroeconomic prospects; but reaping the benefits while avoiding economic problems would depend, in particular, on sound fiscal policies. The paper looks at the role of wage and employment policies within the broader civil service reform agenda. It also analyzes wage bill developments since the 1990s and proposes steps to accelerate pay and civil service reforms.